A Decade of Archaeological Exploration on the Temple Mount. (2nd January 2018) - Baruch, Yuval; Reich, Ronny; Sandhaus, Débora
Abstract : Recent inspection by the Israel Antiquities Authority has shed light on several issues related to the history of the Temple Mount in Jerusalem:important data has been gathered regarding the character of the rock at the summit of the hill; knowledge of the drainage systems and the cisterns that have served the Temple Mount has been augmented; in several places ancient structures buried beneath layers of soil have been recorded; and several previously concealed architectural elements probably associated with the Second Temple period have been detected.